Detecção do vírus da diarreia viral bovina em carrapatos Rhipicephalus (Boophilus) microplus alimentados e, bovino persistentemente infectado - Almeida, Laura Lopes de; Marques, Fernanda Simone; Reck Junior, José; Santos, Adriana da Silva; Gomes, Danilo Carloto; Vaz Junior, Itabajara da Silva; Driemeier, David; Canal, Cláudio Wageck (Acta Scientiae Veterinariae, 2018)
Background : : : : Bovine viral diarrhea virus (BVDV) is one of the main agents that cause economical losses in cattle worldwide. Congenitally infected calves that are born persistently infected (PI) to BVDV are the main sources of infection to susceptible cattle. Direct contact is the most important form of transmission, but indirect contact can also spread BVDV, not only inside herds, but also between them. Transmission of BVDV by haematophagous insects has been proven experimentally, but the role of ticks in the transmission of BVDV has never been investigated. Ticks can heavily infest cattle raised in tropical areas and Rhipicephalus (Boophilus) microplus is the most important among them. The present experiment was carried out to investigate the role of R. microplus ticks in the transmission of BVDV, experimentally infecting PI calf with ticks. Material, Methods and Results: Three calves were used in the experiment: one PI calf was identified from a natural outbreak; a second animal was infested with the progeny of a tick fed on the PI calf and the third was kept as a negative control, infested with negative ticks. Viral RNA investigation was performed by reverse transcription followed by polymerase chain reaction (RT-PCR) from the sera of the calves and from ticks (adult females, eggs and larvae that were the progeny of the experimentally contaminated adult females and from the control animal). BVDV RNA was detected in tick adult females fed on the PI calf, but not in the control animal. Experimental infestation of a second cattle with larvae derived from adult females infected with BVDV was not able to produce infection. These data suggest that the virus is able to pass to ticks during feeding on the infected PI animal, but that there is no transmission by transovarial route, as viral RNA was not detected in eggs and larvae from adult females infected with BVDV. Discussion: Bovine tick is the most important ectoparasite in domestic animals in tropical and subtropical areas. However, its role in transmission of viral agents, particularly BVDV, has not been previously studied. The results of our experiment suggested that adult females of R. microplus were not able to transmit the infection to susceptible cattle. However, a macerate of a pool of tick females fed on the PI calf was positive to BVDV. A further validation using a larger number of infested bovines would help to confirm this new finding. R. microplus ticks are monoxenic, but it must be considered that the males, different from females, make a non-continual process of blood sucking and may move between bovines to reproduce. Additionally, in conditions of close contact between animals, besides tick males, larvae may change hosts in the early stages of development. These facts do not permit to exclude the risk of direct spread of viral infection in the herd by a same specimen of R. microplus. On the other hand, the presence of virus inside females represents an environmental reservoir of BVDV, which may infect through epithelial abrasions if ingested. These considerations may be reinforced by the fact that in field conditions it has been observed that high animal density favors the fast spread of BVDV in cattle herds. Collectively, these evidences suggest that ticks would represent an additional factor to be allowed for in BVDV transmission. As a conclusion, the present study demonstrates that R. microplus can be contaminated with BVDV during blood feeding, strengthening the idea that haematophagous vectors can be involved in the spread of the disease. In spite of the fact that BVDV was not transmited by the progeny of the ticks, it is not possible to discard such form of transmission under natural conditions.